Biographical Projects and the Reconstruction of Cross-Channel Lives: Progress and Challenges - Vivienne LARMINIE (E-REA)
Compared with the late nineteenth century Dictionary of National Biography (DNB), the Oxford Dictionary of National Biography (Oxford DNB) presents a fuller picture of the lives of British people abroad, whether it be their education, travel or exile. Similarly, the experience of, and contribution by, French-born immigrants or visitors to Britain is better appreciated. The electronic version of the dictionary, with its advanced searching facility, allows the retrieval of information on groups of people born or temporarily resident in particular places and preliminary evaluations of the effects of movements of people, books, ideas and occupational skills. Oxford DNB and other projects like the History of Parliament, which is currently at work on the lives of all MPs in the period 1640–1660, have benefited from the opening up of archives to an international audience, at first through the printing of records, and later through the availability of catalogues and documents online. Lives have been illuminated; understanding has been enriched. However, it is clear that much more remains to be discovered. Careers contain lacunae where men and women disappear from the geographical map. The sharing of information by scholars working on discrete aspects of the period, and the extension of databases to complement valuable contemporary printed material now available, are both critical if impressions of extensive and important interpenetration of cultures are to be tested and evaluated.